Nogo‐A controls structural plasticity at dendritic spines by rapidly modulating actin dynamics. Issue 6 (5th February 2016) - Kellner, Yves; Fricke, Steffen; Kramer, Stella; Iobbi, Cristina; Wierenga, Corette J.; Schwab, Martin E.; Korte, Martin; Zagrebelsky, Marta
ABSTRACT: Nogo‐A and its receptors have been shown to control synaptic plasticity, including negatively regulating long‐term potentiation (LTP) in the cortex and hippocampus at a fast time scale and restraining experience‐dependent turnover of dendritic spines over days. However, the molecular mechanisms and the precise time course mediating these actions of Nogo‐A are largely unexplored. Here we show that Nogo‐A signaling in the adult nervous system rapidly modulates the spine actin cytoskeleton within minutes to control structural plasticity at dendritic spines of CA3 pyramidal neurons. Indeed, acute Nogo‐A loss‐of‐function transiently increases F‐actin stability and results in an increase in dendritic spine density and length. In addition, Nogo‐A acutely restricts AMPAR insertion and mEPSC amplitude at hippocampal synaptic sites. These data indicate a crucial function of Nogo‐A in modulating the very tight balance between plasticity and stability of the neuronal circuitry underlying learning processes and the ability to store long‐term information in the mature CNS. © 2016 Wiley Periodicals, Inc.